Goldenseal (Hydrastis canadensis L.) and its active constituents: A critical review of their efficacy and toxicological issues. (October 2020) - Mandal, Sudip Kumar; Maji, Amal Kumar; Mishra, Siddhartha Kumar; Ishfaq, Pir Mohammad; Devkota, Hari Prasad; Silva, Ana Sanches; Das, Niranjan
Graphical abstract: Highlights: Goldenseal is widely used as a traditional medicinal herb and food supplement. Goldenseal alkaloids including berberine showed numerous of therapeutic effects. Critically evaluated the pharmacological and toxicological effects of goldenseal and berberine. Also evaluated the pharmacokinetic profile and food safety efficacy of goldenseal. Further detailed research is necessary to provide scientific evidences for unelucidated mechanisms. Abstract: Goldenseal ( Hydrastis canadensis L.) is a medicinal plant widely used in various traditional systems of medicine and as a food supplement. It has been traditionally used by Native Americans as a coloring agent and as medicinal remedy for common diseases and conditions like wounds, digestive disorders, ulcers, skin and eye ailments, and cancer. Over the years, goldenseal has become a popular food supplement in the USA and other regions. The rhizome of this plant has been used for the treatment of a variety of diseases including, gastrointestinal disorders, ulcers, muscular debility, nervous prostration, constipation, skin and eye infections, cancer, among others. Berberine is one of the most bioactive alkaloid that has been identified in different parts of goldenseal. The goldenseal extract containing berberine showed numerous therapeutic effects such as antimicrobial, anti-inflammatory, hypolipidemic, hypoglycemic, antioxidant, neuroprotective (anti-Alzheimer's disease), cardioprotective, and gastrointestinal protective. Various research finding suggest the health promoting effects of goldenseal components and their extracts. However, few studies have also suggested the possible neurotoxic, hepatotoxic and phototoxic activities of goldenseal extract and its alkaloids. Thus, large randomized, double-blind clinical studies need to be conducted on goldenseal supplements and their main alkaloids to provide more evidence on the mechanisms responsible for the pharmaceutical activity, clinical efficacy and safety of these products. Thus, it is very important to review the scientific information about goldenseal to understand about the current scenario.